INVESTIGATION OF THE CHARACTER VALUE TOLERANCE IN MULTICULTURAL LEARNING IN ELEMENTARY SCHOLL - Idayanti, Zulfi; Suleman, Muh. Asharif (Jurnal Ilmiah Pendidikan Citra Bakti, 2024)
Instilling the character values of tolerance in multicultural learning is a process of integrating attitudes of mutual respect and acceptance of differences in culture, religion, ethnicity, and other backgrounds in education. Therefore, this study aims to determine the validity of the instrument for instilling the character values of tolerance in multicultural learning. Data were obtained through the PISA database, 2018 edition, with code numbers SC017 and SC061. Data were analyzed with the help of the JASP (Jeffrey's Amazing Statistics Program) application with the CFA (Confirmatory Factor Analysis) analysis method. This study used primary data with 335 respondents from schools in Indonesia. The indicators used to measure the character value instillation instrument are the curriculum and multicultural learning. The CFI value = 0.999, NFI = 0.985, IFI = 0.999, and RNI = 0.999 have also been in accordance with the criteria applied to obtain the fit model. Thus, the character value instillation instruments whose validity was tested is included as fit. The implications of this study indicate that valid and fit assessment instruments can be applied in Indonesian schools to instill tolerance values through a multicultural curriculum. This helps policymakers and educators develop more inclusive and tolerant education programs, supporting harmonious living in diverse societies.